2022
DOI: 10.1542/peds.2021-053852d
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve Immunization Coverage Among Children and Adolescents: A Meta-analysis

Abstract: BACKGROUND AND OBJECTIVES Vaccinations are recognized as a feasible, cost-effective public health intervention for reducing the burden and associated mortality of many infectious diseases. The purpose of this study was to evaluate the effectiveness of potential interventions to improve the uptake of vaccines among children and adolescents. METHODS We performed a literature search until December 2020. Eligible studies were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 124 publications
1
7
1
Order By: Relevance
“…Our review also shows that caregivers who attained some level of education have higher odds of acceptance compared to those who never attended school. This finding echoes the results of previous studies, which showed that attainment of a higher level of education among mothers is a leading predictor of full immunization coverage [ 4 , 37 ] and that health education interventions targeting caregivers significantly increased parental attitudes toward vaccines [ 38 , 39 ] and immunization coverage [ 40 , 41 ]. Therefore, vaccine education campaigns targeting caregivers with a lower level of education may go a long way in improving the acceptance of the RTS,S malaria vaccines among caregivers.…”
Section: Discussionsupporting
confidence: 87%
“…Our review also shows that caregivers who attained some level of education have higher odds of acceptance compared to those who never attended school. This finding echoes the results of previous studies, which showed that attainment of a higher level of education among mothers is a leading predictor of full immunization coverage [ 4 , 37 ] and that health education interventions targeting caregivers significantly increased parental attitudes toward vaccines [ 38 , 39 ] and immunization coverage [ 40 , 41 ]. Therefore, vaccine education campaigns targeting caregivers with a lower level of education may go a long way in improving the acceptance of the RTS,S malaria vaccines among caregivers.…”
Section: Discussionsupporting
confidence: 87%
“…Maternal education has been shown to positively contribute to child health and associated immunization service uptake [ 28 , 29 ]. A meta-analysis found that education about vaccinations through counseling sessions and printable information materials increased overall vaccination coverage by 19% [ 30 ]. In the same meta-analysis, interventions for providers, such as training for health staff and reminders for end-users, were shown to improve vaccine coverage by 13% [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contextualized pro-equity urban immunization interventions will result in faster advances toward the IA2030 targets, and work to halt and slow down current backsliding and fragility in immunization systems. Additionally, many of the results point to the room for multisectoral and integrated interventions, as many of the determinants related to low immunization coverage point to potential interventions on gender barriers, education barriers, and systems strengthening [32,34,35]. Tools such as the urban immunization toolkit are being used by several countries to complement existing immunization guidelines by tailoring immunization planning, implementing, and monitoring approaches to meet challenging contexts in urban areas, especially in slum environments; many such tools are available to support these efforts globally [35].…”
Section: Discussionmentioning
confidence: 99%